VIRECHANA PASCHAT SHATAVARI GHRITA UTTARA VASTI IN KSHEENA SHUKRA- A CASE STUDY - Rupesh Vilas, Patil (International Journal of Ayurveda and Pharma Research, 2016)
Oligozoospermia is a condition in which sperm count is less than 20 millions/ml associated with motility defects; accounts for about 90% of male infertility cases and its prevalence is increasing in the current era. In about 30-40% cases, the cause of oligozoospermia is unknown. In Ayurvedic parlance, the condition is referred as Ksheena Shukra; a Vaata pitta vitiation disorder affecting the volume and concentration of Shukra with associated complaints like Maithuna ashakti, Medhra vrushana vedana. Ayurvedic management includes Shodhana therapy along with Uttara vasti administration. A male patient presented with inability to beget a child due to low sperm count (< 10 million/ml) and sperm motility (< 30%) detected in previous two semen analyses along with reduced sexual desire and inability to sustain erection. Snehapaana with Shatavari ghrita, followed by Virechana with Kalyanaka gudam and later Uttara Vasti with Shatavari Ghrita administered in 7 sittings after initial administration of 2 Madhutailika Vasti resulted in significant increase in sperm count (>50 millions/ ml) and motility (>50%).  A significant improvement in sexual desire, sustained erection till the completion of sexual act was noticed and testicular pain along with post coital exhaustion was completely relieved. This case indicates that Ksheena shukra condition can be treated successfully with Panchakarma intervention namely Snehapaana, Virechana and Uttara vasti.